The macroeconomic effects of fiscal policy - Afonso, António (2010)
We investigate the macroeconomic effects of fiscal policy using a Bayesian Structural Vector Autoregression approach. We build on a recursive identification scheme, but we: (i) include the feedback from government debt (ii); look at the impact on the composition of output; (iii) assess the effects on asset markets (via housing and stock prices); (iv) add the exchange rate; (v) assess potential interactions between fiscal and monetary policy; (vi) use quarterly data, particularly, fiscal data; and (vii) analyze empirical evidence from the U.S., the U.K., Germany, and Italy. The results show that government spending shocks, in general, have a small effect on GDP; lead to important "crowding-out" effects; have a varied impact on housing prices and generate a quick fall in stock prices; and lead to a depreciation of the real effective exchange rate. Government revenue shocks generate a small and positive effect on both housing prices and stock prices that later mean reverts; and lead to an appreciation of the real effective exchange rate. The empirical evidence also shows that it is important to explicitly consider the government debt dynamics in the model.